Posterior Root Repair of Medial Meniscus Combined With Valgus Opening Wedge Tibial Osteotomy - José Leonardo Rocha de Faria, M.D., M.Sc.; Douglas Mello Pavão, M.D., M.Sc.; Marcos de Castro Moreirão, M.D.; Victor Elias Titonelli, M.D., M.Sc.; Eduardo Branco de Sousa, M.D., M.Sc., Ph.D.; Sandra Tie Nishibe Minamoto, M.D., M.Sc.; Marcelo Mandarino, M.D., M.Sc.; Alan de Paula Mozella, M.D., M.Sc. (Arthroscopy Techniques, 2021)
The medial meniscal root tear, a particular meniscal injury at the level of its posterior bone insertion, leads to a loss of impact absorption and load distribution capacity, similar to total meniscectomy. Therefore, its repair is fundamental for knee joint longevity. This type of injury often occurs in middle-aged patients with lower limbs varus malalignment, which results in mechanical overloading of the medial compartment and induces premature cartilage wear out. The success of meniscal root repair, with meniscal bone reinsertion, depends on the correction and realignment of varus deformities greater than 5° for physiological levels. In this situation, corrective tibial osteotomy combined with meniscal repair is indicated. Our goal is to describe the step-by-step technique of the valgus opening wedge tibial osteotomy combined with the arthroscopic reinsertion of the posterior meniscal root in tibia during the treatment of a patient with varus deformity and medial meniscus root tear.